Is there a relation between clinical scores and serum ion levels after MoM-THA? One year results in 383 implants.: Clinical scores and serum ion levels after MoM-THA - Pogliacomi, Francesco; Schiavi, Paolo; Calderazzi, Filippo; Leigheb, Massimiliano; Domenichini, Marco; Pedrazzini, Alessio; Ceccarelli, Francesco; Vaienti, Enrico (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: Adverse reaction to metal debris is the major cause of the high revision rates of metal on metal hip implants with femoral head size ≥ 36mm. Health authorities recommend regular surveillance even for asymptomatic individuals. The main investigations used are Co+ and Cr+ serum levels, x-rays and, eventually, ultrasound and MARS-MRI. Clinic is also assessed. The aim of this study is to identify if there is a relation between  ion levels and the clinical scores  in order to evaluate the outcome and  plan the correct management after this type of implant.Methods: 383 subjects were included and divided in 3 groups (serum ion levels >, 60 µg/L). Co+, Cr+, HHS and OHS results of 1 2017 were analysed in order to show a correlation between ion levels and clinical scores .Results: Clinical scores were similar in group 1 and 2. Differences were observed comparing the group 1 and 2 with group 3 for both variables.Discussion and Conclusions: Surveillance algorithms have been introduced by health  authorities. Nevertheless, the indication to revision surgery is not simple especially in those cases in which a discrepancy between clinic and investigations is present. In this study clinical scores seem to be less important than ion levels in the evaluation of outcomes and in order to plan the correct management in the majority of cases. Larger studies are needed to highlight the real importance of clinical scores in the decision making after these type of implants.